The Representation of Racism in the Film Pengepungan di Bukit Duri (A Semiotic Analysis Based on Roland Barthes’ Model) - Dani Fitrah Kurniawan; Nursapia Harahap (CV. AFDIFAL MAJU BERKAH, 2026)
This study is motivated by the persistence of racism in society, which does not always manifest explicitly but is reproduced through communication practices and media representations. The research problem addressed in this study is how racist communication is represented in the film Pengepungan di Bukit Duri. This study aims to analyze the forms of racist communication in the film as a system of meaning operating through verbal and visual signs. The method employed is a qualitative approach using Roland Barthes’ semiotic analysis, which examines meaning at the levels of denotation, connotation, and myth. The data consist of scenes containing racist communication, collected through observation and analyzed purposively. The results show that racist communication is represented through labeling, stereotypes, microaggressions, hate speech, as well as dehumanization and collective violence against the Chinese ethnic group. Within the framework of the race discrimination system, racism operates at the interactional, social, and structural levels, which are interconnected. The novelty of this study lies in its analysis of racism as a communication practice based on a system of signs that is linked to social structures. Thus, the film not only represents conflict but also reveals how racism is normalized through communication. This study contributes to communication studies by positioning racism as a sign-based communicative system linked to broader social structures